INTELLIGENT FIRE ALARM SYSTEM ONBOARD SHIP - Azhar Othman; W. N. Hazlini; Anis F.G.; A.G Othman (Marine Frontier, 2021)
Fires onboard ship is one of the most severe threats onboard ship, life-threatening, and cause property losses due to the presence of flammable material such as liquid fuel and electrical equipment that makes ships susceptible to fires. This paper proposed a design of an intelligent fire alarm system onboard ship and the system performance was analysed by measuring the delay time needed for the system to respond. The circuit mastermind, Arduino UNO, controls the fire detection using GSM technology subjected to the temperature and smoke sensors. MQ2 sensor detects combustible gas and smoke presence; meanwhile, LM35 detect heat changes. GSM works in the communication part, sending SMS to the users. This system controls and monitors each sensor's capability through microcontroller and system software. When the smoke or temperature input reaches a threshold value, the system detects a potential fire outbreak. It will immediately send an SMS alert to the users and simultaneously activate the buzzer upon the possible fire outbreak. This system helps protect lives and properties from fire consequences by immediately responding to prevent fire incidents onboard ships.